INSTITUTIONAL AND LEGAL SUPPORT FOR THE FORMATION AND IMPLEMENTATION OF THE BUDGETARY POLICY OF THE TERRITORIES DEVELOPMENT IN UKRAINE (World of finance, 2020)
Introduction. The issue of institutional legal support of formation and implementation of the budget policy of territorial development is extremely important at the present stage of the state development and decentralization processes that are taking place.The purpose is to study the institutional and legal support for the formation and implementation of budget policy for the development of the territories of Ukraine and to develop proposals for reforming the system of inter-budgetary relations and changes to the basics of budget regulation.Results. It was determined that subsidiarity is one of the key principles of organization of functions in the sphere of public administration, which is one of the main principles of organization of power institutions. The main directions of reforming the administrative and territorial structure of the country are outlined. The basic legislative acts which today form the legal basis for forming the budgetary policy of territorial development in Ukraine in the context of decentralization and reform of public finances are analyzed, namely the laws on amendments to the Budget and Tax Codes of Ukraine. The main priorities of the state regional policy were investigated according to the Law of Ukraine "On the Principles of State Regional Policy". Definition of powers of subjects of the state regional policy, directions of coordination of activities of the governing bodies of different levels and mechanism of their financing are considered. The reform of the system of intergovernmental relations is analyzed in detail.Conclusions. Creation of a decentralized territorial development policy requires usage of a systematic approach that targets directly all participants in the process with institutional compliance and mandatory state-level delegation of mandate.